2017
DOI: 10.1590/1983-21252017v30n422rc
|View full text |Cite
|
Sign up to set email alerts
|

WATER AND SALT STRESSES ON GERMINATION OF COWPEA ( Vigna unguiculata cv. BRS Tumucumaque) SEEDS

Abstract: -The objective of this work was to evaluate seeds of cowpea, cultivar BRS Tumucumaque, subjected to different water stresses induced by polyethylene glycol (PEG-6000) and mannitol and different salt stresses induced by NaCl and CaCl 2 solutions. The water and salt stresses was evaluated in laboratory using completely randomized experimental designs in 2x6 factorial arrangements, with six osmotic potentials (0.0, -0.2, -0.4, -0.6, -0.8 and -1.0 MPa) and two stress inducers for each experiment, with four replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
2
6
0
3
Order By: Relevance
“…Similar results have also been reported by other researchers, who found that an osmotic potential of -0.9 MPa after PEG, NaCl or mannitol treatment led to a reduction in maize and soybean seed germination (Abreu et al, 2014;Soares et al, 2015). A decline in cowpea (Vigna unguiculata) seed viability, vigor and quality was also reported by Ferreira et al (2017) when the osmotic potentials were below -0.6 MPa.…”
Section: Resultssupporting
confidence: 89%
“…Similar results have also been reported by other researchers, who found that an osmotic potential of -0.9 MPa after PEG, NaCl or mannitol treatment led to a reduction in maize and soybean seed germination (Abreu et al, 2014;Soares et al, 2015). A decline in cowpea (Vigna unguiculata) seed viability, vigor and quality was also reported by Ferreira et al (2017) when the osmotic potentials were below -0.6 MPa.…”
Section: Resultssupporting
confidence: 89%
“…In the present work, the decrease of seed germination rate was indeed more evident that the decline in germination (%, six days after sowing) and one of the most pronounced parameters under study. This result is in accordance with other cowpea studies, where the seed germination rate (GR) also decreased with drought stress induced by PEG-6000 (Araújo et al, 2018;Ferreira et al, 2017;Murillo-Amador et al, 2002). Several cowpea genotypes revealed significant alterations in their germination with PEG-6000 treatments, while others were not so affected, suggesting that distinct genotypes could be differently disturbed by drought.…”
Section: Tablesupporting
confidence: 92%
“…Water deficit simulation using PEG 6000 also allowed to observe the effects of stress on germination and initial growth of seedlings of the cowpea cultivar BRS Tumucumaque, by the reduction in the evaluated variables (Ferreira et al, 2017).…”
Section: Resultsmentioning
confidence: 99%